A Study on the Mechanical Properties of Oil Palm Mesocarp Fibre-Reinforced Thermoplastic. (14th March 2016) - Olusunmade, Olusola Femi; Adetan, Dare Aderibigbe; Ogunnigbo, Charles Olawale
Abstract : Oil palm mesocarp fibre obtained from a palm oil processing mill was washed with detergent and water to remove the oil and sun-dried to enhance good adhesion to Linear Low Density Polyethylene (LLDPE). The fibre was pulverized and filtered through a sieve of pore size 300 microns. The Oil Palm Mesocarp Fibre Reinforced Thermoplastic (OPMFRT) was produced with a form of hand lay-up method and varying fibres weight ratio in the matrix from 5 wt% to 25 wt% in steps of 5 wt%. Tensile test was carried out to determine the tensile strength, tensile modulus, and elongation at break of the material. The hardness and impact strength of the composite were also determined. The results showed that tensile modulus and hardness of the OPMFRT increased by 50% and 24.56%, respectively, while tensile strength, impact strength, and percentage elongation of the OPMFRT decreased by 36.78%, 39.07%, and 95.98%, respectively, as fibre loading increased from 5 wt% to 25 wt%. The study concluded that the application of the OPMFRT developed should be restricted to areas demanding high rigidity and wear resistance.